Impactos da diversidade de gênero na alta gestão e da responsabilidade social na agressividade fiscal de empresas brasileiras - Pessoa, Francisca Everlene Nogueira (2019)
Management actions designed to reduce tax payments are increasingly becoming a characteristic of the corporate landscape, in which companies, seeking to maximize results, can engage in activities of tax aggressiveness, which consists of activities favorable to the reduction of taxes and actions carried out to avoid tax payments and/or obtain tax benefits (HANLON; HEITZMAN, 2010). In this context, and under the precepts of Stakeholder and Legitimacy Theories, by which organizations must consider the needs of stakeholders and legitimize their actions to evidence the compliance with the existing social contract between organizations and society, gender diversity in organizations and corporate social responsibility can be recognized as factors that affect the tax aggressiveness of companies. In the light of FOREGOING, the research aims to investigate the influence of gender diversity on top management and corporate social responsibility on the aggressiveness of Brazilian companies. This research is descriptive, quantitative and documentary, with a sample composed by 83 companies listed in B3 S.A., whose data were extracted from the Financial Statements, Reference Forms, Economática® and CSRHub® databases. In addition to descriptive statistics, it was used the multivariate analysis of multiple correspondence analysis (MCA) and multiple linear regression with panel data, considering a time horizon of five years (2013-2017). The study is justified by the widening of the debate about tax aggressiveness, in an institutional context which tax authorities, shareholders and the general public are concerned with corporate tax responsibility (HUSEYNOV; KLAMM, 2012). The results indicated a negative influence of the female presence on the executive board and of corporate social responsibility and its social and corporate governance dimensions in the tax aggressiveness of companies, indicating that those with greater gender diversity on top management and socially responsible behavior are less aggressive with the purpose of fulfilling their social responsibilities and acquiring legitimacy. However, the environmental dimension of corporate social responsibility has shown a positive influence on tax aggressiveness, suggesting that companies can intentionally increase their environmental activities to protect themselves against possible reputational risks arising from aggressive tax activities. Thus, in general terms, the female presence and socially responsible behavior are aligned with a concern with the interests of stakeholders and the legitimacy of the company in front of society, ratifying the recommendations of the literature regarding the effects of the characteristics of the companies and the management behavior in tax decisions in the context of Brazilian companies, where the legal and economic environment can open space for opportunistic behavior, such as aggressive tax activities.